Characterization of an Nmr homolog that modulates GATA factor-mediated nitrogen metabolite repression in Cryptococcus neoformans. - I Russel Lee; Jonathan W C Lim; Kate L Ormerod; Carl A Morrow; James A Fraser (PLoS ONE, 2012)
Nitrogen source utilization plays a critical role in fungal development, secondary metabolite production and pathogenesis. In both the Ascomycota and Basidiomycota, GATA transcription factors globally activate the expression of catabolic enzyme-encoding genes required to degrade complex nitrogenous compounds. However, in the presence of preferred nitrogen sources such as ammonium, GATA factor activity is inhibited in some species through interaction with co-repressor Nmr proteins. This regulatory phenomenon, nitrogen metabolite repression, enables preferential utilization of readily assimilated nitrogen sources. In the basidiomycete pathogen Cryptococcus neoformans, the GATA factor Gat1/Are1 has been co-opted into regulating multiple key virulence traits in addition to nitrogen catabolism. Here, we further characterize Gat1/Are1 function and investigate the regulatory role of the predicted Nmr homolog Tar1. While GAT1/ARE1 expression is induced during nitrogen limitation, TAR1 transcription is unaffected by nitrogen availability. Deletion of TAR1 leads to inappropriate derepression of non-preferred nitrogen catabolic pathways in the simultaneous presence of favoured sources. In addition to exhibiting its evolutionary conserved role of inhibiting GATA factor activity under repressing conditions, Tar1 also positively regulates GAT1/ARE1 transcription under non-repressing conditions. The molecular mechanism by which Tar1 modulates nitrogen metabolite repression, however, remains open to speculation. Interaction between Tar1 and Gat1/Are1 was undetectable in a yeast two-hybrid assay, consistent with Tar1 and Gat1/Are1 each lacking the conserved C-terminus regions present in ascomycete Nmr proteins and GATA factors that are known to interact with each other. Importantly, both Tar1 and Gat1/Are1 are suppressors of C. neoformans virulence, reiterating and highlighting the paradigm of nitrogen regulation of pathogenesis.